The use of anesthetics for cesarean section delivery in women in Duhok, Kurdistan region, Iraq - Karam, Rozheen Shukry; Mohammad, Fouad K. (Journal of Ideas in Health, 2022)
Background: Limited information is available on anesthetics that are preferred or used by anesthesiologists for cesarean section (CS) delivery in Kurdistan region, Iraq. This study aims to document general or regional anesthesia use in elective CS deliveries in four major hospitals in Duhok province, Northern Iraq. Methods: A retrospective cross-sectional study was conducted from February 2019 to February 2020. The general and regional anesthetics types were recorded for each CS delivery case within the selected hospitals. Any adjuvants and medications used with the anesthetics were also recorded. Univariate and bivariate analyses were undertaken. The statistically significant was considered at less than 0.05. Results: A total of 3420 elective CS deliveries were reported. The mean age ± SD of the pregnant women was 29.6 ± 5.8 years. The anesthetics used in the four hospitals were propofol as a general anesthetic (53.0%) and bupivacaine as a spinal anesthetic (47.0%). The combination of propofol and bupivacaine was used only in 0.3%. The three most frequently and concurrently used adjuvants and medications with propofol or bupivacaine were metoclopramide (90.0%), dexamethasone (80.0%), and ephedrine (73.0%). Conclusion: Propofol and bupivacaine were the general and spinal anesthesia of choice, respectively, for elective CS delivery in Duhok province, northern Iraq. Some adjuvants and medications were supplemented to improve the quality of anesthesia and the outcome of CS delivery.